1995
DOI: 10.1002/ajmg.1320600316
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia: A genome scan targets chromosomes 3p and 8p as potential sites of susceptibility genes

Abstract: Using a systematically ascertained sample of 57 families, each having 2 or more members with a consensus diagnosis of schizophrenia (DSM-III-R criteria), we have carried out linkage studies of 520 loci, covering approximately 70% of the genome for susceptibility loci for schizophrenia. A two-stage strategy based on lod score thresholds from simulation studies of our sample identified regions for further exploration. In each region, a dense map of highly informative dinucleotide repeat polymorphisms (heterozygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
135
2
4

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 245 publications
(147 citation statements)
references
References 42 publications
6
135
2
4
Order By: Relevance
“…The human FZD3 gene is located on chromosome 8p21, a linkage locus containing a putative gene for schizophrenia (Pulver et al, 1995;Blouin et al, 1998;Kendler et al, 2000;Gurling et al, 2001). Candidate gene association studies in this region have shown that SNPs within the FZD3 gene are strongly associated with schizophrenia in Chinese Han (Yang et al, 2003;Zhang et al, 2004), as well as in Japanese descents (Katsu et al, 2003).…”
Section: Schizophrenia and Polymorphisms In Frizzled 3 And Gsk3bmentioning
confidence: 99%
“…The human FZD3 gene is located on chromosome 8p21, a linkage locus containing a putative gene for schizophrenia (Pulver et al, 1995;Blouin et al, 1998;Kendler et al, 2000;Gurling et al, 2001). Candidate gene association studies in this region have shown that SNPs within the FZD3 gene are strongly associated with schizophrenia in Chinese Han (Yang et al, 2003;Zhang et al, 2004), as well as in Japanese descents (Katsu et al, 2003).…”
Section: Schizophrenia and Polymorphisms In Frizzled 3 And Gsk3bmentioning
confidence: 99%
“…7,[12][13][14][15][16][17][18][19][20][21][22] Fine mapping and haplotype analysis of the linkage peak in an Icelandic sample identified a haplotype, shared by seven out of the thirty-three families tested, implicating an B600 kb region. 7 A core haplotype from this region (Hap ICE ) spanning 290 kb and consisting of five singlenucleotide polymorphisms (SNPs) and two microsatellite markers was found to be over-represented in affected individuals (P = 0.000087, one-tailed; Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…8 In total, 17 complete or nearly complete genome scans for schizophrenia have now been published. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] None of these scans have revealed large single-gene effects. Concordance rates for schizophrenia in monozygotic twins are far short of 100% stressing the importance of environmental factors.…”
Section: Introductionmentioning
confidence: 99%